2017
DOI: 10.3389/fimmu.2017.01508
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Supports the Suppressive Immune Responses Elicited by Regulatory T Cells

Abstract: Interleukin-4 (IL-4) has been considered as one of the tolerogenic cytokines in many autoimmune animal models and clinical settings. Despite its role in antagonizing pathogenic Th1 responses, little is known about whether IL-4 possesses functions that affect regulatory T cells (Tregs). Tregs are specialized cells responsible for the maintenance of peripheral tolerance through their immune modulatory capabilities. Interestingly, it has been suggested that IL-4 supplement at a high concentration protects respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 54 publications
(53 reference statements)
5
45
0
1
Order By: Relevance
“…Notably, MCS patients frequently report co-morbidities, such as hay fever, asthma and atopic dermatitis [3,10]. Moreover, IL-4 plays a role in antagonizing pathogenic Th1 responses [40]. The increased IL-4 serum levels observed in MCS patients recruited for this study and in other studies [9,10], and the here observed significant positive correlation with IFN-γ levels, suggest a compensative reaction to buffer the increase of IFN-γ production.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Notably, MCS patients frequently report co-morbidities, such as hay fever, asthma and atopic dermatitis [3,10]. Moreover, IL-4 plays a role in antagonizing pathogenic Th1 responses [40]. The increased IL-4 serum levels observed in MCS patients recruited for this study and in other studies [9,10], and the here observed significant positive correlation with IFN-γ levels, suggest a compensative reaction to buffer the increase of IFN-γ production.…”
Section: Discussionsupporting
confidence: 58%
“…IL-4 is a cytokine associated with the activation of Th2 cells, and has long been considered as one of the tolerogenic cytokines in many autoimmune animal models and clinical settings; however, its overproduction has mainly been associated with the development of allergic reactions and atopy [40]. Notably, MCS patients frequently report co-morbidities, such as hay fever, asthma and atopic dermatitis [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…The key DAGs contributing to this cluster included B2M, IGHG3, IL7R, ETS1, RPS19, and TNFAIP3. The pathway enrichment for the SLE DIME network includes pathways that are heavily described in the literature for SLE, such as the neutrophil degranulation pathways or NETosis 3741 , interleukin 4 and interleukin 13 signaling 42,43 , TLR signaling pathway 44 , translocation of ZAP70 to immunological synapsis 45 , and immune-regulatory interactions between lymphoid and non-lymphoid cells ( Supplementary Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the e-cigs users, a significant association between LLM and lung inflammatory cytokines IL-4 and IL-10 was found, but not other cytokines associated with smoking [14] . Unlike the other cytokines that were tested, IL-4 and IL-10 play a role as an immune suppressor and are required to avoid inflammation and maintain tissue homeostasis [ 18 , 19 ]. IL-4 promotes macrophage activation into the M2 phenotype, and M2 macrophages produce IL-10 [20] .…”
Section: Discussionmentioning
confidence: 99%